8-O-Acetyl Shanzhiside Methylester From Lamiophlomis Rotata Reduces Neuropathic Pain by Inhibiting the ERK/TNF-α Pathway in Spinal Astrocytes - Zhang, Wei; Bai, Yang; Qiao, Yu; Wang, Jian; Li, Meng-Ying; Wang, Jing-Wen; Jia, Na; Chen, Tao; Li, Yun-Qing; Wen, Ai-Dong (Frontiers in Cellular Neuroscience, 2018)
Lamiophlomis rotata (Benth.) Kudo is an effective traditional herb in the clinical treatment of chronic pain syndromes in China. 8-O-acetyl shanzhiside methylester (8-OaS), a chief component in Lamiophlomis rotata, possesses potent immunosuppressive activities and favorable analgesic effects. This study was proposed to compare the analgesic effects of 8-OaS with those of lidocaine and ketamine in a spinal nerve ligation (SNL) model by behavioral tests, and then investigated its effects upon the expression of spinal glial fibrillary acidic protein (GFAP), phosphorylated extracellular regulated protein kinases (pERK) and tumor necrosis factor-alpha (TNF-α) via immunofluorescence staining and western blot analyses. The data showed consecutive intrathecal injection of 8-OaS for two weeks brought about remarkable palliation of neuropathic pain, possessing similar anti-allodynia effects with those of lidocaine and ketamine. Two weeks after surgery, pERK within the spinal dorsal horn was mainly expressed in astrocytes more than neurons and microglia, and 8-OaS inhibited spinal astrocytic activation and TNF-α expression. Finally, co-treatment of 8-OaS and PD98059 (an ERK inhibitor) did not lead to remarkable increase in pain relief or TNF-α expression comparing to rats treated with 8-OaS or PD98059 alone. In conclusion, the anti-nociceptive effects of 8-OaS in the condition of neuropathic pain relied on the inhibition of SNL-induced astrocyte activation, probably via the down-regulation of the ERK/TNF-α pathway.